Mutational Profile Using Next-Generation Sequencing May Aid in the Diagnosis and Treatment of Urachal Adenocarcinoma. (February 2020) - Cornejo, Kristine M.; Cosar, Ediz F.; Paner, Gladell P.; Yang, Ping; Tomaszewicz, Keith; Meng, Xiuling; Mehta, Vikas; Sirintrapun, Sahussapont Joseph; Barkan, Guliz A.; Hutchinson, Lloyd
Objectives . The rare urachal adenocarcinoma (UAC) of the bladder has striking morphologic and immunohistochemical overlap with colorectal adenocarcinoma (CAC) and bladder adenocarcinoma (BAC). To date, the mutational status in UAC and BAC has not been well investigated. Methods . We retrospectively evaluated 34 UACs (mucinous, n = 9; intestinal, n = 3; signet ring cell, n = 1; not otherwise specified, n = 21) and 4 BACs (n = 4). Next-generation sequencing analysis of 50 cancer "hotspot" gene mutations using the Ampliseq Cancer Hotspot Panel v2 was performed. Two UAC cases did not have adequate DNA quality with poor sequencing coverage and were excluded from the study. Results. RAS mutations were identified in 16 of 32 (50%) UACs (15 KRAS ; 1 NRAS ) and none of the BACs (0%). TP53 mutations were found in both UACs (18/32; 56%) and BACs (4/4; 100%). GNAS (n = 4), SMAD4 (n = 3), and BRAF (n = 1) mutations were only found in UACs. In contrast, APC (n = 2) mutations were only found in BACs. The mucinous subtype of UAC contained a SMAD4 mutation in 33% of cases (3/9), which was not identified in any other subtype (0/23; 0%) ( P = .0169). The only BRAF mutation was identified in the single signet ring cell subtype of UAC. There were no other differences in the mutation profile when comparing histologic subtypes of UAC. Conclusions . In summary, UAC and BAC have overlapping but distinct mutation profiles and these differences may aid in separating these 2 entities. Next-generation sequencing to identify therapeutic targets or resistance markers may aid treatment decisions.